Optical study of orbital excitations in transition-metal oxides - Rückamp, Reinhard; Haverkort, Maurits W. (New journal of physics, 2005)
The orbital excitations of a series of transition-metal compounds are studied by means of optical spectroscopy. Our aim was to identify signatures of collective orbital excitations by comparison with experimental and theoretical results for predominantly local crystal-field excitations. To this end, we have studied TiOCl, RTiO 3 (R = La, Sm and Y), LaMnO 3 , Y 2 BaNiO 5 , CaCu 2 O 3 and K 4 Cu 4 OCl 10 , ranging from early to late transition-metal ions, from t 2g to e g systems, and including systems in which the exchange coupling is predominantly three-dimensional, one-dimensional or zero-dimensional. With the exception of LaMnO 3 , we find orbital excitations in all compounds. We discuss the competition between orbital fluctuations (for dominant exchange coupling) and crystal-field splitting (for dominant coupling to the lattice). Comparison of our experimental results with configuration-interaction cluster calculations in general yields good agreement, demonstrating that the coupling to the lattice is important for a quantitative description of the orbital excitations in these compounds. However, detailed theoretical predictions for the contribution of collective orbital modes to the optical conductivity (e.g. the line shape or the polarization dependence) are required to decide on a possible contribution of orbital fluctuations at low energies, in particular, in case of the orbital excitations at ≈0.25 eV in RTiO 3 . Further calculations are called for which take into account the exchange interactions between the orbitals and the coupling to the lattice on an equal footing.
Gesehen am 08.11.2017